RELACIONES INTERGUBERNAMENTALES EN COLOMBIA - Barbosa Cardona, Octavio (Cuadernos de Administración, 2006)
The Intergovernmental Relations -IGR- are defined as the crossed reciprocal or hierarchic activities, between the different instances and levels of the State in its function of government. When governing, the State takes part by means of determination of public policy, process that in Colombia, is developed in the context of, on one hand, the the precariousness of the territorial unfolding of the State, given the insufficient levels of coordination and complementarity between the different levels of government, in the incomplete political decentralization,and, on the other hand, by the disfunctions of the administrative apparatus, derived from the institutional weakening in the disordered process of modernization.